A wireless rowing measurement system for improving the rowing performance of athletes - Hohmuth, R.; Schwensow, D.; Malberg, H.; Schmidt, M. (Sensors, 2023)
The rowing technique is a key factor in the overall rowing performance. Nowadays the athletes` performance is so advanced that even small differences in technique can have an impact on sport competitions. To further improve the athletes` performance, individualized rowing is necessary. This can be achieved by intelligent measurement technology that provides direct feedback. To address this issue, we developed a novel wireless rowing measurement system (WiRMS) that acquires rowing movement and measures muscle activity using electromyography (EMG). Our measurement system is able to measure several parameters simultaneously: the rowing forces, the pressure distribution on the scull, the oar angles, the seat displacement and the boat acceleration. WiRMS was evaluated in a proof-of-concept study with seven experienced athletes performing a training on water. Evaluation results showed that WiRMS is able to assess the rower`s performance by recording the rower`s movement and force applied to the scull. We found significant correlations (p < 0.001) between stroke rate and drive-to-recovery ratio. By incorporating EMG data, a precise temporal assignment of the activated muscles and their contribution to the rowing motion was possible. Furthermore, we were able to show that the rower applies the force to the scull mainly with the index and middle fingers.